THE CLINICAL COMPREHENSIVE PRACTICE EVALUATION SYSTEM OF PHYSIOTHERAPY STUDENTS DIPLOMA-IV BINAWAN UNIVERSITY - Noraeni Arsyad; Dinny Devi Triana (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2021)
This study aims to describe the problems of the clinical practice assessment system are not in accordance with standards which has an impact on the results of Binawan University Diploma IV physiotherapy graduate. Some items in measuring devices to assess the clinical performance of physiotherapy students have low responsive level. To solve this problem, this study uses descriptive qualitative methods with case study approach that uses various sources of information in gathering data to provide conclusions or detailed descriptions. Data is collected through in-depth interviews with student, clinical instructors and document observations. Data analysis through reduction techniques, presenting data and giving conclusions through triangulation of sources, data and methods by connecting the suitability of relevant theories with the data obtained. The results of the study are generally illustrated the assessment system has been running more focused on case reports, general competency and group comprehensive test assessments. It was found that lack of an independent clinical performance assessment to see individual competencies related to learning outcome from implementation of comprehensive practice physiotherapy clinic. Thus the findings are expected to improve and evaluate the implementation of clinical comprehensive practice evaluation system of physiotherapy students Diploma IV Binawan University